Pris de court 14 films court - Félicioli, Jean-Loup; Gagnol, Alain
14 animated films by Alain Gagnol and Jean-Loup Felicioli ... A unique design, original and colorful ... for dark, cruel and desperate stories ... [www.heeza.fr]